The Penguin dictionary of physics - Illingworth, Valerie (New York, N.Y., USA : Penguin Books, 1991)
Presents 4,500 definitions of terms used in the various disciplines of physics, including synonyms and abbreviations.
"First published 1977"--T.p. verso.
Adult
Keywords: Physics -- Dictionaries; Physics -- Dictionaries